Pengaruh Rasio Profitabilitas, Likuiditas, Leverage dan Aktivitas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Pertambangan di BEI Periode 2020-2023 - Putri, Jihan Latifi; Laila Wardani (Postgraduate, University of Mataram, 2025)
This study aims to test and analyze the moderating effect of company size on the influence of Return On Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset TurnOver (TATO) on company value in mining companies listed on the Indonesia Stock Exchange for the period 2020-2023. This type of research is causal associative research (cause and effect) with a data collection method, namely a survey sample. Sampling in this study used a purposive sampling technique with certain criteria so that a sample of 30 companies was obtained with a research period from 2020-2023. The data analysis method used to solve the problems in this study is panel data regression analysis with the help of the Eviews 12 program. The results of this study indicate that Return On Equity (ROE) has a positive and significant effect on company value, Current Ratio (CR) has a positive and insignificant effect on company value, Debt to Equity Ratio (DER) has a positive and insignificant effect on company value, Total Asset Turn Over (TATO) has a positive and significant effect on company value, Total Asset (TA) is able to moderate the effect of Return On Equity (ROE) on company value, Total Asset (TA) is unable to moderate the effect of Current Ratio (CR) on company value, Total Asset (TA) is able to moderate the effect of Debt to Equity Ratio (DER) on company value, Total Asset (TA) is unable to moderate the effect of Total Asset TurnOver (TATO) on company value.